WACANA KEAGAMAAN REMAJA DI MEDIA SOSIAL (Kajian Analisis Wacana Model Van Dijk dalam Tulisan Afi) - Muzakki, Hawwin (LP3M STAI DARUSSALAM LAMPUNG, 2017)
Religious discourse is a sequence of related sentences, and relates one proposition to another proposition, thus forming a unified language of religion. Religious discourse is influenced by the age level, the development of psychological aspects, including the development of thinking. Adolescence is a period of transition between childhood and adulthood. In addition, as a search for self-identity especially related to religion. Like teenagers in general, Afi Nihaya Faradisa also wrote his religious anxiety that became viral on Facebook. The purpose of this study is actually to see the religious discourse of adolescents in social media, using a qualitative approach, discourse analysis van Dijk model. Van Dijk divides his discourse into three dimensions: text dimension, social cognition, and social context. There is one Afi writings that the author thoroughly titled Inheritance. The result found that Afis writing took the perspective of a teenager who wrote about religion on facebook themed pluralism, mysticism, convergence, religious conflict and nationalism. Afis writing also sparked debate in Indonesian society. Afis writing is not born positivist but constructivist, because it is built by the understanding of writing of others. The implications of this study are to see how a teen considers religion and government steps in guarding youth religious behavior. Keywords: Religious, youth, media, discourse analysis